Corporate governance and climate change: policy, innovation, strategies, and legitimacy - Rodriguez Jasso, Alan Francisco; García Flores, Francisco; Briseño García, Arturo (CIENCIA ergo-sum; Vol. 31 (2024): CIENCIA ergo-sumDO - 10.30878/ces.v31n0a5, 2024)
This study is intended to understand the governance practices addressed in the literature to address climate change, identifying common variables, methods, regions, and sources of information that facilitate the framing of novel analyses for researchers and practitioners. We perform a systematic review of 45 studies between 1980 and 2019 published in Web of Science. The results suggest that policy, innovation, operations, and legitimacy are common variables in addressing climate change. Our findings show that Ordinary Least Squares and Panel Data are the most frequent methods developed in the literature. Emerging economies such as India, Brazil, Indonesia, Iran, South Korea, and Mexico offer an interesting context to explore. The climate crisis has become one of the major threats to modern society.